Systemic inflammatory regulators and age-related macular degeneration: a bidirectional Mendelian randomization study - Liu, Xi; Cao, Yu; Wang, Ying; Kang, Lihua; Zhang, Guowei; Zhang, Junfang; Qin, Bai; Yang, Ling; Luo, Jiawei; Li, Pengfei; Geng, Wenjing; Ji, Min; et al. (Frontiers in Genetics, 2024)
IntroductionWe investigated the relationship between systematic regulators of inflammation and the risk of age-related macular degeneration (AMD), both wet and dry forms, by using bidirectional, two-sample Mendelian randomization (MR).MethodsWe performed bidirectional two-sample Mendelian randomization analysis using genome-wide study (GWAS) data for 91 plasma proteins from 14,824 individuals of European descent across 11 study groups. Next, we utilized data from the FinnGen consortium to study AMD using the inverse- variance-weighted approach for Mendelian randomization. Additional analyses involved MR-Egger, Weighted median, Weighted mode, MR-PRESSO, and MR- Steiger filtering techniques.ResultsWe identified 16 cytokines associated AMD outcomes and post FDR correction, higher levels of fibroblast growth factor 19 and leukemia inhibitory factor receptor were associated with decreased risk for AMD, while higher levels of tumour necrosis factor ligand superfamily member 14 were associated with increased risk for AMD. Additionally, higher levels of interleukin-10 receptor subunit alpha were associated with decreased risk for wet AMD, higher levels of leukemia inhibitory factor receptor were associated with decreased risk for dry AMD, and higher levels of signaling lymphocytic activation molecule were associated with increased risk for dry AMD. Genetic susceptibility to AMD was associated with elevated levels of TNF-related activation-induced cytokines (TNFSF11), and genetic susceptibility to wet AMD was associated with elevated levels of TNFSF11, interleukin-18 receptor 1 (IL18R1), and CUB domain-containing protein 1 (CDCP1).DiscussionThis research enhances our understanding of systemic inflammation in AMD, providing insights into etiology, diagnosis, and treatment of AMD and its forms.